2006
DOI: 10.1017/s0033291706008099
|View full text |Cite
|
Sign up to set email alerts
|

Long-term predictors of outcome in fatigued employees on sick leave: a 4-year follow-up study

Abstract: Background. Persistent fatigue is strongly associated with functional status and can lead to absenteeism and work disability. Despite several prognostic studies on chronic fatigue, little attention has been paid to occupational outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 27 publications
1
12
0
Order By: Relevance
“…That disability was the main independent predictor of discontinuation of employment in a multivariable model is consistent with a study of employees on long-term sick leave due to fatigue [26]. Our finding suggests that people with CFS/ME continue in employment despite the primary (fatigue and pain) and secondary effects (depression and anxiety) of CFS/ME.…”
Section: Discussionsupporting
confidence: 91%
“…That disability was the main independent predictor of discontinuation of employment in a multivariable model is consistent with a study of employees on long-term sick leave due to fatigue [26]. Our finding suggests that people with CFS/ME continue in employment despite the primary (fatigue and pain) and secondary effects (depression and anxiety) of CFS/ME.…”
Section: Discussionsupporting
confidence: 91%
“…This was confirmed by the above-mentioned evaluation of treatments in the NHS CFS clinics (n = 1643) by Crawley et al [45]. Leone et al [56] found that physical functioning at baseline, deterioration of physical functioning between the baseline measurement and 12-month follow-up predicted work disability at 4-year follow-up. Hill et al [47] who studied the natural history of severe ME, concluded that the prognosis for recovery was extremely poor.…”
Section: Illness Severitymentioning
confidence: 65%
“…In two studies with 18 months and three-year follow-up respectively, employment status decreased from 31% to 24% [49] and from 63% to 55% [34]. In a study with a follow-up of 3.8 years, 36.5% (19/52) of CFS like cases returned to work [56]. In a nine-year follow-up by Anderson et al [33], as a group, patients had not improved.…”
Section: Employment Status In Me/cfsmentioning
confidence: 93%
See 1 more Smart Citation
“…CBT [10], or 48 months [11] of follow-up. We previously reported on short-term and long-term predictors of fatigue, work status, and chronic fatigue syndrome in the course of time [12][13][14].…”
Section: Introductionmentioning
confidence: 99%